Flexible Geschäftsmodelle in der Telekommunikation und die Netzneutralitätsdebatte - Thomas Fetzer; Martin Peitz; Heike Schweitzer (Wirtschaftsdienst, 2013)
Die Einführung neuer Endkundentarife für den festen Internetzugang durch die Deutsche Telekom hat die Netzneutralitätsdebatte erneut befeuert. Dabei geht es um die Frage, ob Endkundenanbieter bei der Übertragung von Daten im Internet bestimmte Dienste oder Inhalte gegen ein vom Sender oder Empfänger zu zahlendes Entgelt priorisieren dürfen. Sowohl auf nationaler als auch auf europäischer Ebene wurden Verordnungsentwürfe vorgelegt, die ein offenes Internet sicherstellen sollen. Dieser Beitrag untersucht zum einen, inwieweit Internetvolumentarife wie die der Deutschen Telekom tatsächlich Netzneutralitätsfragen aufwerfen. Zum anderen wird der nationale Entwurf einer Netzneutralitätsverordnung ebenso wie die entsprechenden Regelungen im Verordnungsentwurf der Europäischen Kommission einer ersten kritischen Würdigung unterzogen. – – The net neutrality debate concerns the differential treatment of data on the Internet and the pricing models used by enduser internet service providers (IPSs). In particular, end-user ISPs may want to prioritize certain services and charge on the sender or the receiver side for this activity. In the policy debate it is asked whether regulatory intervention is warranted to restrict such behavior. The introduction of new end-user tariffs for fi xed-line Internet access by Deutsche Telekom has heated up the debate in Germany. At the national level, the German Ministry of Economics and Technology has prepared a draft regulation on net neutrality, which aims at limiting the differential treatment of data transmission on the internet including the access networks and, thus, to protect the 'Open Internet'. The European Commission has prepared an alternative draft regulation for a single European market in telecommunications, which contains provisions for an 'Open Internet'. In this article, the authors investigate the extent to which the new tariff structure by Deutsche Telekom relates to the net neutrality debate. They also provide a fi rst critical analysis of the proposals by the German Ministry of Economics and Technology and the European Commission.
Keywords: K21; K23; L13; L42; L51; 330; Telekommunikationsnetz; Netzregulierung; Preismanagement; Telekommunikationssektor; Deutschland